The Rationality of Antibiotics Use on Acute Diarrhea to Pediatric Inpatients in the Fatmawati Hospital for 2018-2019 Period: Studi Penggunaan Obat Antibiotik Rational pada Diare Akut untuk Pasien Rawat Inap Anak di RS. Fatmawati Periode 2018-2019 - Rokhmah, Nisa Najwa; Manuel, Yovania Grace Priskila; Putri Kusuma, Ema Nillafita; Nurdin, Naufal Muharam (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: Diarrhea is characterized by an increase in the frequency of bowel movements more than three times a day. This disease has a fairly high incidence rate in Indonesia, especially in children. One of the causes of diarrhea is a bacterial infection, therefore it needs to be treated with antibiotics. Several studies show that there are still many antibiotics that are used irrationally. It is necessary to analyze the rationality of the use of antibiotics in pediatric patients with diarrhea using the Gyssens method Objectives: This study is to ascertain the profile of acute diarrhea pediatric patients characteristic and evaluate antibiotics rationality with Gyssens method. Moreover, the purpose of this study is to analyze the factors that influence the rationality of the use of antibiotics in the inpatient pediatric acute diarrhea installation of Fatmawati Hospital 2018-2019 period. Material and Methods: This study is descriptive observational research. The study design was cross-sectional with retrospective data collection which was analysed then qualitatively with the Gyssens flow method Results: The result showed 54,29% antibiotics usde appropriately and rational. The irrational use of antibiotics was 45.7%. The results of statistical analysis with chi-square show a significant relationship between the rationality of antibiotics and the type of antibiotic (Ï = 0.000 < 0.05) and multiple logistic regression analysis showed that the route of drug administration (Ï = 0.000 < 0.05) affected the rationality of antibiotics use. Conclusions: Less than 50% of the patients received irrational treatment according to the Gyssen flow chart and according to the results of statistical analysis, the type of antibiotic and the route of drug administration affected the rationality of antibiotics.